Friction material, application of friction material, brake pad and preparation method of brake pad

By using specific friction materials to prepare the mining elevator gate plate, the problem of insufficient fire-proof and anti-static performance of the brake pads in the mine is solved, good flame retardant and conductive properties are achieved, and the safe operation of the mine is ensured.

CN119463326APending Publication Date: 2025-02-18SHANDONG GOLD PHOENIX
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411621125.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Mining machinery works in flammable and explosive underground mines. The fire-proof and anti-static properties of the brake pads may cause explosion accidents, threatening the life safety of operators and the stable operation of the mine.

Method used

Provide a friction material, containing bisphenol A epoxy resin, flame retardant rubber, flame retardant expandable graphite, white carbon black, barite powder, aramid fiber, halogen modified flame retardant fiber, flame retardant magnesium hydroxide and other groups It is used to prepare mining elevator gate sheets and is prepared by kneading mixture hot pressing.

Benefits of technology

This friction material has good conductivity and flame retardancy, can effectively prevent electrostatic sparks and fires, ensure the safe operation of mining elevators, and does not contain asbestos, lead and other banned substances, and is an environmentally friendly friction material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463326A_ABST
    Figure CN119463326A_ABST
Patent Text Reader

Abstract

The invention provides a friction material and application thereof as well as a brake pad and a preparation method thereof, and relates to the technical field of mining machinery. The invention discloses a friction material. The friction material is composed of the following components: 8%-17% of bisphenol A epoxy resin, 12%-20% of flame-retardant rubber, 2%-5% of flame-retardant expandable graphite, 3%-10% of white carbon black, 20%-30% of barite powder, 3%-5% of aramid fiber, 18%-28% of halogen modified flame-retardant fiber, 4%-6% of flame-retardant magnesium hydroxide, 0.5%-1.5% of polystyrene resin, 0.5%-1.5% of hexamethylenetetramine, 0.5%-1.5% of an anti-aging agent and 0.5%-2% of an accelerant. The friction material provided by the invention does not contain metal fibers, does not damage a brake pair, does not have brake sparks, and is suitable for a mining elevator brake pad; and the friction material does not contain asbestos, lead and compounds thereof, hexavalent chromium and other prohibited substances, belongs to an environment-friendly friction material, and is environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mining machinery, and in particular to a friction material and a use thereof, a brake pad and a preparation method thereof. Background Art

[0002] Mining machinery operates in flammable and explosive underground mines, which places extremely high demands on the fireproof and anti-static properties of brake pads. This is mainly because the underground mine environment is special and there are a lot of flammable gases and dust. Once the brake pads generate sparks or static electricity during operation, it may cause serious explosion accidents, posing a huge threat to the life safety of operators and the stable operation of mines. In view of this special working environment, the design and production of mining machinery brake pads need to use special materials and processes to ensure that they have good fireproof and anti-static properties. Summary of the invention

[0003] In view of the above problems existing in the prior art, the present invention provides a friction material and its use, a brake pad and its preparation method to improve the performance of the brake pad of the hoist.

[0004] To achieve the above-mentioned purpose and other related purposes, the first aspect of the present invention provides a friction material, which is composed of the following raw material components, measured by mass percentage of the friction material: 8% to 17% bisphenol A epoxy resin, 12% to 20% flame retardant rubber, 2% to 5% flame retardant expandable graphite, 3% to 10% white carbon black, 20% to 30% barite powder, 3% to 5% aramid fiber, 18% to 28% halogen-modified flame retardant fiber, 4% to 6% flame retardant magnesium hydroxide, 0.5% to 1.5% polystyrene resin, 0.5% to 1.5% hexamethylenetetramine, 0.5% to 1.5% antioxidant, and 0.5% to 2% accelerator.

[0005] In one embodiment of the present invention, the flame retardant expandable graphite includes any one or more of natural flake graphite, artificial graphite and colloidal expandable graphite.

[0006] In one embodiment of the present invention, the flame retardant expandable graphite is a composition of the natural flake graphite, the artificial graphite and the colloidal expandable graphite, and the mass ratio of the natural flake graphite, the artificial graphite and the colloidal expandable graphite is 3:1:2.

[0007] In one embodiment of the present invention, the flame retardant rubber comprises aluminum hydroxide modified rubber, and the content of aluminum hydroxide in the aluminum hydroxide modified rubber is 10-30% based on the total mass of the aluminum hydroxide modified rubber.

[0008] In one embodiment of the present invention, the antioxidant includes any one of antioxidant A, antioxidant D, and antioxidant 4010; the accelerator includes any one of accelerator M, accelerator DM, accelerator TMTD, and accelerator CZ.

[0009] A second aspect of the present invention provides a use of a friction material, wherein the friction material is used for a brake pad of a mining hoist.

[0010] A third aspect of the present invention provides a brake pad for a mining hoist, comprising a friction block made of the above-mentioned friction material.

[0011] A fourth aspect of the present invention provides a method for preparing a brake pad for a mining hoist, comprising the following steps:

[0012] Mixing of raw materials of friction material: weigh the above friction material according to proportion and place it in a kneader to stir evenly, add alcohol, knead and stir until mixed evenly, and dry; based on the mass percentage of the friction material, the added amount of the alcohol is 15-20% of the friction material, and the content of the alcohol after drying is less than 0.8% of the friction material.

[0013] Hot pressing: Put the steel back and the evenly mixed friction material into a hot press to form a semi-finished brake pad;

[0014] Heat treatment: put the brake pad semi-finished product into an oven, heat it to 180-300° C. and keep it warm for 3 hours to obtain the brake pad.

[0015] In one embodiment of the present invention, during the raw material mixing of the friction material, the drying temperature is 60-80° C. and the drying time is 2-3 hours.

[0016] In one embodiment of the present invention, during the hot pressing forming, the pressing pressure is 3-5 MPa, the hot pressing temperature is 130-160° C., and the hot pressing time is 2-10 min.

[0017] The friction material provided by the present invention does not contain metal fibers, does not damage the brake pair, does not cause brake sparks, and is suitable for brake pads for mining hoists; in addition, the friction material of the present invention does not contain prohibited substances such as asbestos, lead and its compounds, hexavalent chromium, etc., and is an environmentally friendly friction material. The brake pad of the present application includes a friction block made of the above friction material, and the brake pad has a stable friction coefficient, high shear strength, low wear, and does not damage the brake pair. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.

[0019] Figure 1 The present invention is a flow chart of the preparation of a mine hoist brake pad in one embodiment. DETAILED DESCRIPTION

[0020] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0021] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.

[0022] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.

[0023] The brake pads for mine hoists are an important part of the brake system of mine hoists. Their main function is to generate braking force through friction with the brake disc when the hoist is working, so as to control the running speed of the hoist and achieve parking. For comprehensive reasons such as braking safety, environmental protection, and personal health, the technical document MTT 113-1995 for brake pads for mine hoists makes the following requirements for the flame retardant and antistatic properties of the friction body of brake pads for underground coal mines and mine hoists:

[0024] Table 1 Flame retardant and antistatic properties of brake pad friction body

[0025]

[0026] At the same time, for environmental protection considerations, the brake pad friction body should not use asbestos, lead or its compounds and other materials that may harm human health and may produce harmful gases, dust or compounds. Therefore, the present application provides a friction material that not only has good braking performance and good flame retardancy, but also meets environmental protection requirements and greatly reduces harm to the human body.

[0027] The friction material provided by the present invention is composed of the following raw material components, calculated by mass percentage of the friction material: 8% to 17% of bisphenol A epoxy resin, 12% to 20% of flame retardant rubber, 2% to 5% of flame retardant expandable graphite, 3% to 10% of white carbon black, 20% to 30% of barite powder, 3% to 5% of aramid fiber, 18% to 28% of halogen-modified flame retardant fiber, 4% to 6% of flame retardant magnesium hydroxide, 0.5% to 1.5% of polystyrene resin, 0.5% to 1.5% of hexamethylenetetramine, 0.5% to 1.5% of antioxidant and 0.5% to 2% of accelerator.

[0028] In one embodiment of the present invention, the flame retardant expandable graphite includes any one or more of natural flake graphite, artificial graphite and colloidal expandable graphite, for example, any one of natural flake graphite, artificial graphite or colloidal expandable graphite, or any combination of natural flake graphite, artificial graphite and colloidal expandable graphite. Preferably, the flame retardant expandable graphite is a composition of natural flake graphite, artificial graphite and colloidal expandable graphite, preferably, the mass ratio of natural flake graphite, artificial graphite and colloidal expandable graphite is 3:1:2. Both natural flake graphite and artificial graphite have good electrical conductivity, so the friction material has good electrical conductivity. During the braking process, the static electricity generated will be transmitted to the ground at the first time, thereby avoiding sparks generated by static electricity and preventing the ignition of combustible gases in the mine from causing safety accidents. Colloidal expandable graphite has good flame retardant properties. Together with bisphenol A epoxy resin, flame retardant rubber, halogen-modified flame retardant fiber, and flame retardant magnesium hydroxide, the friction material has good flame retardant properties, even in a fire or spark environment.

[0029] In one embodiment of the present invention, the flame retardant rubber includes aluminum hydroxide modified rubber. Based on the total mass of the aluminum hydroxide modified rubber, the content of aluminum hydroxide in the aluminum hydroxide modified rubber is 10-30%, for example, any value between 10%, 20% or 30%.

[0030] In one embodiment of the present invention, the antioxidant includes any one of antioxidant A, antioxidant D, and antioxidant 4010; the accelerator includes any one of accelerator M, accelerator DM, accelerator TMTD, and accelerator CZ. In other embodiments, the antioxidant and accelerator may also be other types of antioxidants and accelerators in the art.

[0031] The present invention provides a use of a friction material. The friction material of the present invention does not contain metal fibers, does not damage a brake pair, has no braking sparks, and is suitable for brake pads of mining hoists. In addition, the friction material of the present invention does not contain prohibited substances such as asbestos, lead and its compounds, hexavalent chromium, etc., and is an environmentally friendly friction material that is friendly to the environment.

[0032] The present invention provides a brake pad for a mining hoist, which includes a friction block made of the above-mentioned friction material. The friction material of the present application has moderate hardness, and the brake pad has high shear strength, low wear and tear, and does not damage the brake pair.

[0033] See also Figure 1 The present application provides a method for preparing a brake pad for a mine hoist, comprising the following steps:

[0034] S1. Mixing the raw materials of the friction material: weigh the friction material according to the proportion and place it in a kneader to stir it evenly, add alcohol, knead and stir until the mixture is evenly mixed, and dry it; the amount of alcohol added is 15-20% of the friction material by mass percentage, and the alcohol content after drying is less than 0.8% of the friction material.

[0035] S2, hot pressing: putting the steel back and the evenly mixed friction material into a hot press to press and form a brake pad semi-finished product;

[0036] S3. Heat treatment: Place the semi-finished brake piece into an oven, heat it to 180-300°C and keep it warm for 3 hours.

[0037] In step S1, the friction material is prepared according to the ratio of 8% to 17% of bisphenol A epoxy resin, 12% to 20% of flame retardant rubber, 2% to 5% of flame retardant expandable graphite, 3% to 10% of white carbon black, 20% to 30% of barite powder, 3% to 5% of aramid fiber, 18% to 28% of halogen-modified flame retardant fiber, 4% to 6% of flame retardant magnesium hydroxide, 0.5% to 1.5% of polystyrene resin, 0.5% to 1.5% of hexamethylenetetramine, 0.5% to 1.5% of antioxidant, and 0.5% to 2% of accelerator, based on the mass percentage of the raw material components of the friction material. In one embodiment, the particle size of barite is greater than 95% of its total amount passing through a 325-mesh sieve, the particle size of polystyrene resin is greater than 95% of its total amount passing through a 325-mesh sieve, and the flame retardant magnesium hydroxide has a D10 ≥ 1.0 μm, a D50 of 3.0 to 13.0 μm, and a D90 ≤ 40.0 μm.

[0038] In terms of the mass percentage of the friction material, the amount of alcohol added can be any value between 15% and 20% of the friction material, such as 15%, 18% or 20%. In one embodiment, the drying temperature after adding alcohol and mixing evenly is 60 to 80°C, such as 60°C, 70°C or 80°C, such as any value between 60°C and 80°C; the drying time is 2 to 3h, such as 2h, 2.5h or 3h, such as any value between 2 to 3h. In the present application, a conventional kneading machine in the art is selected for stirring. Adding alcohol during the mixing process can better mix and fuse the components of the friction material.

[0039] In step S2, the pressing pressure is 3-5 MPa, such as 3 MPa, 4 MPa or 5 MPa, etc., any value in the range of 3-5 MPa; the hot pressing temperature is 130-160°C, such as 130°C, 140°C, 150°C or 160°C, etc., any value in the range of 130-160°C; the hot pressing time is 2-10 min, such as 2 min, 5 min, 8 min or 10 min, etc., any value in the range of 2-10 min. During hot pressing, a conventional hot press in the art is selected for pressing. The friction material can be placed in the molding cavity of the hot press first, and then the steel back is placed on the surface of the friction material for pressing, or the steel back is placed in the molding cavity of the hot press first, and then the friction material is placed on the surface of the steel back for pressing.

[0040] In step S3, the temperature of the heat treatment may be any value within the range of 180 to 300°C, such as 180°C, 200°C, 250°C, 280°C or 300°C.

[0041] The preparation method of the brake piece of the present invention adopts a kneading and mixing hot pressing method, which has simple process, high operability, low equipment cost and high production efficiency.

[0042] The technical scheme of the present invention is described in detail below through several specific examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.

[0043] Example 1

[0044] The preparation method of the brake pad in this embodiment is as follows: (1) Mixing of raw materials of friction material: in terms of the mass percentage of friction material, the friction material is weighed according to the proportion of 8% bisphenol A epoxy resin, 20% flame retardant rubber, 2% flame retardant expandable graphite, 10% white carbon black, 20% barite powder, 3% aramid fiber, 28% halogen modified flame retardant fiber, 4% flame retardant magnesium hydroxide, 1.5% polystyrene resin, 0.5% hexamethylenetetramine, 1.5% antioxidant, and 1.5% accelerator. The weighed friction material is placed in a kneader and stirred evenly, and then 15% alcohol of the total mass of the friction material is added, stirred for 1 hour to mix evenly, and dried at 60°C for 3 hours, and the alcohol content is 0.44% of the total mass of the friction material. (2) Hot pressing: The steel back and the mixed friction material are placed in a hot press and pressed into shape, with a pressing pressure of 5Mpa, a hot pressing temperature of 160°C, and a hot pressing time of 2min to obtain a semi-finished brake pad. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 200° C. and keep it at this temperature for 3 h to obtain a brake pad.

[0045] In this embodiment, the flame retardant rubber is aluminum hydroxide modified rubber, the content of aluminum hydroxide is 10%, the flame retardant expandable graphite includes natural flake graphite, artificial graphite and colloidal expandable graphite, the mass ratio of natural flake graphite, artificial graphite and colloidal expandable graphite is 3:1:2; the antioxidant is antioxidant A, and the accelerator is accelerator M.

[0046] Example 2

[0047] The preparation method of the brake pad in this embodiment is as follows: (1) Mixing of raw materials of friction material: in terms of mass percentage of friction material, the friction material is weighed according to the proportion of bisphenol A epoxy resin 10%, flame retardant rubber 18%, flame retardant expandable graphite 2.5%, white carbon black 8%, barite powder 24%, aramid fiber 3.5%, halogen modified flame retardant fiber 25.5%, flame retardant magnesium hydroxide 4%, polystyrene resin 1.5%, hexamethylenetetramine 1%, antioxidant 1%, and accelerator 1%. The weighed friction material is placed in a kneader and stirred evenly, and then 16% of the total mass of the friction material is added with alcohol, stirred for 1.5 hours until the mixture is evenly mixed, and dried at 60°C for 2.5 hours. The alcohol content is 0.53% of the total mass of the friction material. (2) Hot pressing: The steel back and the evenly mixed friction material are placed in a hot press and pressed into shape. The pressing pressure is 4Mpa, the hot pressing temperature is 155°C, and the hot pressing time is 4min to obtain a semi-finished brake pad. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 300° C. and keep the temperature for 3 h to obtain a brake pad.

[0048] In this embodiment, the flame retardant rubber is aluminum hydroxide modified rubber, the content of aluminum hydroxide is 25%, the flame retardant expandable graphite includes natural flake graphite, artificial graphite and colloidal expandable graphite, and the mass ratio of natural flake graphite, artificial graphite and colloidal expandable graphite is 3:1:2; the antioxidant is antioxidant D, and the accelerator is accelerator DM.

[0049] Example 3

[0050] The preparation method of the brake pad in this embodiment is as follows: (1) Mixing of raw materials of friction material: in terms of mass percentage of friction material, the friction material is weighed according to the proportion of 12% bisphenol A epoxy resin, 16% flame retardant rubber, 2.5% flame retardant expandable graphite, 6% white carbon black, 27.5% barite powder, 4% aramid fiber, 23.5% halogen modified flame retardant fiber, 5% flame retardant magnesium hydroxide, 1% polystyrene resin, 1.5% hexamethylenetetramine, 0.5% antioxidant, and 0.5% accelerator. The weighed friction material is placed in a kneader and stirred evenly, and then 17% alcohol of the total mass of the friction material is added, stirred for 1.5 hours until the mixture is evenly mixed, and dried at 70°C for 2.5 hours, and the alcohol content is 0.48% of the total mass of the friction material. (2) Hot pressing: The steel back and the evenly mixed friction material are placed in a hot press and pressed into shape, with a pressing pressure of 4Mpa, a hot pressing temperature of 150°C, and a hot pressing time of 5 minutes to obtain a brake pad semi-finished product. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 180° C. and keep it at this temperature for 3 h to obtain a brake pad.

[0051] In this embodiment, the flame retardant rubber is aluminum hydroxide modified rubber, the content of aluminum hydroxide is 20%, the flame retardant expandable graphite includes natural flake graphite, artificial graphite and colloidal expandable graphite, and the mass ratio of natural flake graphite, artificial graphite and colloidal expandable graphite is 3:1:2; the antioxidant is antioxidant 4010, and the accelerator is accelerator TMTD.

[0052] Example 4

[0053] The preparation method of the brake pad in this embodiment is as follows: (1) Mixing of raw materials of friction material: in terms of the mass percentage of friction material, the friction material is weighed according to the proportion of 14% bisphenol A epoxy resin, 15% flame retardant rubber, 4% flame retardant expandable graphite, 4% white carbon black, 28% barite powder, 4.5% aramid fiber, 21% halogen modified flame retardant fiber, 6% flame retardant magnesium hydroxide, 0.5% polystyrene resin, 1% hexamethylenetetramine, 1% antioxidant, and 1% accelerator. The weighed friction material is placed in a kneader and stirred evenly, and then 18% alcohol of the total mass of the friction material is added, stirred for 1.5 hours until the mixture is evenly mixed, and dried at 80°C for 2 hours, and the alcohol content is 0.51% of the total mass of the friction material. (2) Hot pressing: The steel back and the evenly mixed friction material are placed in a hot press and pressed into shape, with a pressing pressure of 4Mpa, a hot pressing temperature of 140°C, and a hot pressing time of 7 minutes to obtain a brake pad semi-finished product. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 250° C. and keep it at this temperature for 3 h to obtain a brake pad.

[0054] In this embodiment, the flame retardant rubber is aluminum hydroxide modified rubber, the content of aluminum hydroxide is 15%, the flame retardant expandable graphite includes natural flake graphite, artificial graphite and colloidal expandable graphite, the mass ratio of natural flake graphite, artificial graphite and colloidal expandable graphite is 3:1:2, the antioxidant is antioxidant 4010, and the accelerator is accelerator CZ.

[0055] Example 5

[0056] The preparation method of the brake pad in this embodiment is as follows: (1) Mixing of raw materials of friction material: in terms of mass percentage of friction material, the friction material is weighed according to the proportion of bisphenol A epoxy resin 17%, flame retardant rubber 12%, flame retardant expandable graphite 5%, white carbon black 3%, barite powder 30%, aramid fiber 5%, halogen modified flame retardant fiber 18%, flame retardant magnesium hydroxide 6%, polystyrene resin 0.5%, hexamethylenetetramine 0.5%, antioxidant 1.5%, and accelerator 1.5%. The weighed friction material is placed in a kneader and stirred evenly, and then 20% of alcohol of the total mass of the friction material is added, stirred for 2 hours until the mixture is evenly mixed, and dried at 70°C for 2 hours, and the alcohol content is 0.56% of the total mass of the friction material. (2) Hot pressing: The steel back and the evenly mixed friction material are placed in a hot press and pressed into shape, with a pressing pressure of 3Mpa, a hot pressing temperature of 130°C, and a hot pressing time of 10 minutes to obtain a brake pad semi-finished product. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 300° C. and keep the temperature for 3 h to obtain a brake pad.

[0057] In this embodiment, the flame retardant rubber is aluminum hydroxide modified rubber, and the content of aluminum hydroxide is 30%; the flame retardant expandable graphite includes natural flake graphite, artificial graphite and colloidal expandable graphite, and the mass ratio of natural flake graphite, artificial graphite and colloidal expandable graphite is 3:1:2; the antioxidant is antioxidant D, and the accelerator is accelerator TMTD.

[0058] Example 6

[0059] The preparation method of the brake pad in this embodiment is as follows: (1) Mixing of raw materials of friction material: in terms of the mass percentage of friction material, the friction material is weighed according to the proportion of 12% bisphenol A epoxy resin, 15% flame retardant rubber, 5% flame retardant expandable graphite, 8% white carbon black, 28% barite powder, 3% aramid fiber, 20% halogen modified flame retardant fiber, 4% flame retardant magnesium hydroxide, 1% polystyrene resin, 1% hexamethylenetetramine, 1% antioxidant, and 2% accelerator. The weighed friction material is placed in a kneader and stirred evenly, and then 15% alcohol of the total mass of the friction material is added, stirred for 1 hour to mix evenly, and dried at 60°C for 3 hours, and the alcohol content is 0.45% of the total mass of the friction material. (2) Hot pressing: The steel back and the evenly mixed friction material are placed in a hot press and pressed into shape, with a pressing pressure of 5Mpa, a hot pressing temperature of 160°C, and a hot pressing time of 2min to obtain a brake pad semi-finished product. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 180° C. and keep it at this temperature for 3 h to obtain a brake pad.

[0060] In this embodiment, the flame retardant rubber is aluminum hydroxide modified rubber, the content of aluminum hydroxide is 15%, the flame retardant expandable graphite is natural flake graphite, the antioxidant is antioxidant A, and the accelerator is accelerator M.

[0061] Example 7

[0062] The preparation method of the brake pad in this embodiment is as follows: (1) Mixing of raw materials of friction material: in terms of the mass percentage of friction material, the friction material is weighed according to the proportion of 15% bisphenol A epoxy resin, 15% flame retardant rubber, 2% flame retardant expandable graphite, 6% white carbon black, 24% barite powder, 4% aramid fiber, 25% halogen modified flame retardant fiber, 5% flame retardant magnesium hydroxide, 1.5% polystyrene resin, 0.5% hexamethylenetetramine, 1% antioxidant, and 1% accelerator. The weighed friction material is placed in a kneader and stirred evenly, and then 20% alcohol of the total mass of the friction material is added, stirred for 2 hours until the mixture is evenly mixed, and dried at 70°C for 2 hours, and the alcohol content is 0.55% of the total mass of the friction material. (2) Hot pressing: The steel back and the evenly mixed friction material are placed in a hot press and pressed into shape, with a pressing pressure of 3Mpa, a hot pressing temperature of 130°C, and a hot pressing time of 10 minutes to obtain a brake pad semi-finished product. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 280° C. and keep it at this temperature for 3 h to obtain a brake pad.

[0063] In this embodiment, the flame retardant rubber is aluminum hydroxide modified rubber, and the content of aluminum hydroxide is 25%; the flame retardant expandable graphite is artificial graphite; the antioxidant is antioxidant D, and the accelerator is accelerator CZ.

[0064] Example 8

[0065] The preparation method of the brake pad in this embodiment is as follows: (1) Mixing of raw materials of friction material: in terms of the mass percentage of friction material, the friction material is weighed according to the proportion of 16% bisphenol A epoxy resin, 14% flame retardant rubber, 4% flame retardant expandable graphite, 7% white carbon black, 20% barite powder, 5% aramid fiber, 24% halogen modified flame retardant fiber, 6% flame retardant magnesium hydroxide, 0.5% polystyrene resin, 1% hexamethylenetetramine, 1.5% antioxidant, and 1% accelerator. The weighed friction material is placed in a kneader and stirred evenly, and then 17% alcohol of the total mass of the friction material is added, stirred for 1.5 hours until the mixture is evenly mixed, and dried at 70°C for 2.5 hours, and the alcohol content is 0.5% of the total mass of the friction material. (2) Hot pressing: The steel back and the evenly mixed friction material are placed in a hot press and pressed into shape, with a pressing pressure of 4Mpa, a hot pressing temperature of 150°C, and a hot pressing time of 5 minutes to obtain a semi-finished brake pad. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 220° C. and keep it at this temperature for 3 h to obtain a brake pad.

[0066] In this embodiment, the flame retardant rubber is aluminum hydroxide modified rubber, the content of aluminum hydroxide is 20%, the flame retardant expandable graphite is colloidal expandable graphite, the antioxidant is antioxidant 4010, and the accelerator is accelerator TMTD.

[0067] Comparative Example 1

[0068] The preparation method of the brake pad in this embodiment is as follows: (1) Mixing of raw materials of friction material: in terms of the mass percentage of friction material, the friction material is weighed according to the proportion of 28% bisphenol A epoxy resin, 2% flame retardant expandable graphite, 10% white carbon black, 20% barite powder, 3% aramid fiber, 28% halogen modified flame retardant fiber, 4% flame retardant magnesium hydroxide, 1.5% polystyrene resin, 0.5% hexamethylenetetramine, 1.5% antioxidant, and 1.5% accelerator. The weighed friction material is placed in a kneader and stirred evenly, and then 15% alcohol of the total mass of the friction material is added, stirred for 1 hour until the mixture is evenly mixed, and dried at 60°C for 3 hours, and the alcohol content is 0.44% of the total mass of the friction material. (2) Hot pressing: The steel back and the evenly mixed friction material are placed in a hot press and pressed into shape, with a pressing pressure of 5Mpa, a hot pressing temperature of 160°C, and a hot pressing time of 2min to obtain a brake pad semi-finished product. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 200° C. and keep it at this temperature for 3 h to obtain a brake pad.

[0069] In this comparative example, the flame retardant rubber is aluminum hydroxide modified rubber, the content of aluminum hydroxide is 18%, the flame retardant expandable graphite includes natural flake graphite, artificial graphite and colloidal expandable graphite, and the mass ratio of natural flake graphite, artificial graphite and colloidal expandable graphite is 3:1:2; the antioxidant is antioxidant 4010, and the accelerator is accelerator CZ.

[0070] Comparative Example 2

[0071] The preparation method of the brake pad in this comparative example is as follows: (1) Mixing of raw materials of friction material: in terms of mass percentage of friction material, the friction material is weighed according to the ratio of 28% flame retardant rubber, 2.5% flame retardant expandable graphite, 8% white carbon black, 24% barite powder, 3.5% aramid fiber, 25.5% halogen modified flame retardant fiber, 4% flame retardant magnesium hydroxide, 1.5% polystyrene resin, 1% hexamethylenetetramine, 1% antioxidant, and 1% accelerator. The weighed friction material is placed in a kneader and stirred evenly, and then 16% alcohol of the total mass of the friction material is added, stirred for 1.5 hours until the mixture is evenly mixed, and dried at 60°C for 3 hours, and the alcohol content is 0.46% of the total mass of the friction material. (2) Hot pressing: The steel back and the evenly mixed friction material are placed in a hot press and pressed into shape, with a pressing pressure of 4Mpa, a hot pressing temperature of 155°C, and a hot pressing time of 4min to obtain a brake pad semi-finished product. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 200° C. and keep it at this temperature for 3 h to obtain a brake pad.

[0072] In this embodiment, the flame retardant rubber is aluminum hydroxide modified rubber, and the content of aluminum hydroxide is 15%; the flame retardant expandable graphite includes natural flake graphite, artificial graphite and colloidal expandable graphite, and the mass ratio of natural flake graphite, artificial graphite and colloidal expandable graphite is 3:1:2; the antioxidant is antioxidant A, and the accelerator is accelerator M.

[0073] Comparative Example 3

[0074] The preparation method of the brake pad in this comparative example is as follows: (1) Mixing of raw materials of friction material: in terms of the mass percentage of friction material, the friction material is weighed according to the proportion of 12% bisphenol A epoxy resin, 16% flame retardant rubber, 6% white carbon black, 30% barite powder, 4% aramid fiber, 23.5% halogen modified flame retardant fiber, 5% flame retardant magnesium hydroxide, 1% polystyrene resin, 1.5% hexamethylenetetramine, 0.5% antioxidant, and 0.5% accelerator. The weighed friction material is placed in a kneader and stirred evenly, and then 17% alcohol of the total mass of the friction material is added, stirred for 1.5 hours until the mixture is evenly mixed, and dried at 60°C for 3 hours, and the alcohol content is 0.47% of the total mass of the friction material. (2) Hot pressing: The steel back and the evenly mixed friction material are placed in a hot press and pressed into shape, with a pressing pressure of 4Mpa, a hot pressing temperature of 150°C, and a hot pressing time of 5 minutes to obtain a brake pad semi-finished product. (3) Heat treatment: Place the brake pad semi-finished product formed by hot pressing in step (2) into an oven, raise the oven temperature to 200° C. and keep it at this temperature for 3 h to obtain a brake pad.

[0075] In this embodiment, the flame retardant rubber is aluminum hydroxide modified rubber, the content of aluminum hydroxide is 20%, the flame retardant expandable graphite includes natural flake graphite, artificial graphite and colloidal expandable graphite, and the mass ratio of natural flake graphite, artificial graphite and colloidal expandable graphite is 3:1:2; the antioxidant is antioxidant D, and the accelerator is accelerator CZ.

[0076] In the above-mentioned Examples 1 to 8 and Comparative Examples 1 to 3, the particle size of barite is 96% of the total amount passing through a 325-mesh sieve, the particle size of polystyrene resin is 96% of the total amount passing through a 325-mesh sieve, the D10 of flame-retardant magnesium hydroxide is 3 μm, the D50 is 10 μm, the D90 is 40 μm, and the particle size of the mixture of friction materials is 50-150 mesh.

[0077] The flame retardancy and surface resistance of the brake pads were tested according to the MTT 113-1995 standard, and the density, compression strength, bending strength, impact strength, elastic modulus, Rockwell hardness and friction coefficient of the brake pads were tested according to the T / CAMET04004.9-2018 standard. The test results are shown in Table 2:

[0078] Table 2 Brake pad performances prepared in Examples 1 to 8 and Comparative Examples 1 to 3 of the present application

[0079]

[0080]

[0081]

[0082] As can be seen from Table 2, the brake pads prepared in Examples 1 to 8 have moderate hardness, high shear strength, and good flame retardant properties, and are suitable for mining hoists. Comparison of Comparative Examples 1 to 3 with Examples 1 to 8 shows that bisphenol A epoxy resin, flame retardant rubber, and flame retardant expandable graphite can synergistically improve the elastic modulus, surface hardness, and flame retardant effect of the brake pads. Furthermore, the strength (impact strength and bending strength) and flame retardant properties of the brake pads prepared in Examples 1 to 5 are better than those in Examples 6 to 8. It can be seen that the synergistic effect of natural flake graphite, artificial graphite, and colloidal expandable graphite can further improve the performance of the brake pads.

[0083] The friction material provided by the present invention does not contain metal fibers, does not damage the brake pair, does not cause brake sparks, and is suitable for brake pads for mining hoists; in addition, the friction material of the present invention does not contain prohibited substances such as asbestos, lead and its compounds, hexavalent chromium, etc., and is an environmentally friendly friction material that is friendly to the environment. The brake pad of the present application includes a friction block made of the above-mentioned friction material, and the friction coefficient of the brake pad is stable, the shear strength is large, the wear amount is small, and it does not damage the brake pair. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.

[0084] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A friction material, characterized in that: Measured in percentage by mass, the friction material is composed of the following raw material components: 8% to 17% bisphenol A epoxy resin, 12% to 20% flame retardant rubber, 2% to 5% flame retardant expandable graphite, 3% to 10% white carbon black, 20% to 30% barite powder, 3% to 5% aramid fiber, 18% to 28% halogen-modified flame retardant fiber, 4% to 6% flame retardant magnesium hydroxide, 0.5% to 1.5% polystyrene resin, 0.5% to 1.5% hexamethylenetetramine, 0.5% to 1.5% antioxidant, and 0.5% to 2% accelerator.

2. The friction material according to claim 1, characterized in that: The flame retardant expandable graphite includes any one or more of natural flake graphite, artificial graphite and colloidal expandable graphite.

3. The friction material according to claim 2, characterized in that: The flame retardant expandable graphite is a composition of the natural flake graphite, the artificial graphite and the colloidal expandable graphite, and the mass ratio of the natural flake graphite, the artificial graphite and the colloidal expandable graphite is 3:1:

2.

4. The friction material according to claim 1, characterized in that: The flame retardant rubber comprises aluminum hydroxide modified rubber, and the content of aluminum hydroxide in the aluminum hydroxide modified rubber is 10-30% based on the total mass of the aluminum hydroxide modified rubber.

5. The friction material according to claim 1, characterized in that: The antioxidant includes any one of antioxidant A, antioxidant D, and antioxidant 4010; the accelerator includes any one of accelerator M, accelerator DM, accelerator TMTD, and accelerator CZ.

6. Use of the friction material according to any one of claims 1 to 5, characterized in that: The friction material is used for brake pads of mine hoists.

7. A brake pad for a mine hoist, characterized in that: The invention comprises a friction block made of the friction material according to any one of claims 1 to 5.

8. A method for preparing a brake pad for a mine hoist according to claim 7, characterized in that: The steps include: Mixing of raw materials of friction material: weigh the friction material according to any one of claims 1 to 5 in proportion and place it in a kneader to stir evenly, add alcohol, knead and stir for 1 to 2 hours until the mixture is evenly mixed, and dry; the amount of alcohol added is 15 to 20% of the friction material by mass percentage, and the content of alcohol after drying is less than 0.8% of the friction material; Hot pressing: Put the steel back and the evenly mixed friction material into a hot press to form a semi-finished brake pad; Heat treatment: put the brake pad semi-finished product into an oven, heat it to 180-300° C. and keep it warm for 3 hours to obtain the brake pad.

9. The preparation method according to claim 8, characterized in that: When the raw materials of the friction material are mixed, the drying temperature is 60-80° C. and the drying time is 2-3 hours.

10. The preparation method according to claim 8, characterized in that: During the hot pressing molding, the pressing pressure is 3-5 MPa, the hot pressing temperature is 130-160° C., and the hot pressing time is 2-10 min.